Evaluation of minerals content of drinking water in Malaysia - Azlan, Azrina; Khoo, Hock Eng; Idris, Mohd Aizat; Ismail, Amin; Razman, Muhammad Rizal (Hindawi Publishing Corporation, 2012)
The drinking and mineral water samples obtained from different geographical locations had concentrations of the selected minerals lower than the standard limits, except for manganese, arsenic, and fluoride. The concentrations of manganese and arsenic in two mineral water samples were slightly higher than the standard international recommended limits. One mineral water sample had a fluoride concentration higher than the standard limits, whereas manganese was not detected in nine drinking and mineral water samples. Most of the selected minerals found in the tap water samples were below the international standard limits, except for iron and manganese. The concentrations of iron and manganese in the tap water samples were higher than the standard limits, which were obtained from one and three of the studied locations, respectively. The potable water obtained from various manufacturers and locations in Peninsular Malaysia is safe for consumption, as the minerals concentrations were below the standard limits prescribed by the Malaysian Food Regulations of 1985. The data obtained may also provide important information related to daily intake of these minerals from drinking water.